A alta progressiva e o retorno de pedófilos para suas famílias - Marafiga, Caroline Velásquez (Universidade do Vale do Rio do Sinos, 2009)
The pedophilia is considered a sexual deviation characterized by intense sexuality behaviors involving humiliation and suffering to children and adolescents. Patients with this diagnosis submitted to legal procedures, in judiciary asylum, have the possibility, in Rio Grande do Sul, to be part of a process called of Progressive Discharge (PD). The PD is a benefit granted by the Judiciary to patients who are complying security measure in judiciary asylums. This practice is a gradual discharge that aims the social reintegration of individuals considered exempt from punishment and who committed crimes. This dissertation addresses questions about the family, education and one perception of PD related to patients, who have committed sexual violence against children and / or adolescents, and who were diagnosed as pedophiles, that were or are going through the process of progressive discharge and are fulfilling their security measures. This study includes four sections, one theoretical, one empirical, a investigation
Keywords: alta progressiva; manicômio judiciário; pedofilia; pedófilos; judiciary asylum; pedophilia; progressive discharge; pedophiles; Ciências Humanas